(untitled) (Estudios Sociales, 2022)
This paper analyzes the links between the labor sphere and the love relationships of gay men. Based on interviews with young gay men in Buenos Aires, Argentina, I lay out three labours of love at the crossroads between work and intimacy. First, the identity negotiation when coming out of the closet through a love relationship. Second, the satisfaction of desire and the role of eroticism in access to work or generating seduction in the workplace. Third, the stabilization of the couple and how employment or unemployment becomes an obstacle to overcome. I conclude with the need to analyze the crossings between love and work both from the form and the content.